FORMULASI DAN AKTIVITAS ANTIBAKTERI SEDIAAN GEL HAND SANITIZER DARI EKSTRAK ETANOL BIJI MANGGA HARUM MANIS ( Mangifera indica L.) TERHADAP Escherichia coli DAN Staphylococcus aureus - Harry Noviardi; Herson Cahaya Himawan; Rina Anggraeni (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Mangifera indica L. is a plant that has antibacterial activity. One of the plant‟s parts that has antibacterial activity on mango is the seed. Natural antibacterial content in the form of tannins contained in ethanol extract of Harum Manis mango seed is considered being effective towards Escherichia coli and Staphylococcus aureus bacteria, which are the main cause bacteria in diarrhea and other skin infections. The objective of this study is to obtain a good and effective formulation to remove Escherichia coli and Staphylococcus aureusbacteria in order to produce natural hand- made antiseptic gel preparations. The diameter of clear zone produced by gel preparation of hand sanitizer ethanol extract of mango seed on Escherichia coli bacteria with gel concentration of 2; 2.5 and 5% respectively - 10.86, 1.74, and 13.15 mm, while on a positive control, it is 7.47 mm. On the other hand, the diameter of clear zone in Staphylococcus aureus with gel concentration of 2; 2.5 and 5% respectively - 10.14, 10.58, and 12.83 mm, while on the positive control, it is 7.43 mm. Based on Anovaone way test followed by Duncan test show a significant difference (significant effect) between the concentration. It can be concluded that the preparation of 70% ethanol extract gel having antibacterial effectiveness towards Escherichia coli and Staphylococcus aureus and effective gel preparation evaluation results are at 2,5% concentration